2016
DOI: 10.1038/ejcn.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum selenium with thyroxin in severely iodine-deficient young children from the Amhara region of Ethiopia

Abstract: Serum Se was negatively associated with T4 level in young children from the Amhara region of Ethiopia and may endanger the effectiveness of the salt iodization program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Today's World. 2017 Feb; 6 (2): 21-26 agreement with a recent study that low selenium level associated with higher concentration of plasma T4 (13,21). In several studies in Iran (12,22,23), Turkey (24,25) and Poland (26), goitrous patients had significant lower Selenium levels than nongoitrous ones.…”
Section: J Biol Today's World 2017 Feb; 6 (2): 21-26 Figure 1 Spesupporting
confidence: 74%
See 2 more Smart Citations
“…Today's World. 2017 Feb; 6 (2): 21-26 agreement with a recent study that low selenium level associated with higher concentration of plasma T4 (13,21). In several studies in Iran (12,22,23), Turkey (24,25) and Poland (26), goitrous patients had significant lower Selenium levels than nongoitrous ones.…”
Section: J Biol Today's World 2017 Feb; 6 (2): 21-26 Figure 1 Spesupporting
confidence: 74%
“…The result of another study in central part of our country revealed that the prevalence of Selenium deficiency in goitrous children was 75.0% and their serum selenium level was 66.86±21.82 (12). In study from Ethiopia, highly selenium deficiency was found in children from the western part of the country but the children in eastern part had little or no selenium deficiency (13). Similar to these studies, the frequency of selenium deficiency and toxicity in china was highly variable in populations of just 20 km apart (14).…”
Section: J Biol Today's World 2017 Feb; 6 (2): 21-26 Figure 1 Spementioning
confidence: 99%
See 1 more Smart Citation
“…Gashu et al . [53] reported Se deficiency risk in school children in the Amhara region of Ethiopia to be 58% (n = 349).…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive and motor impairments observed in konzo, a motor neuron disease associated with cassava cyanogenic exposure in nutritionally challenged African children, may possibly be driven by the combined effects of cyanide toxicity and selenium deficiency (Bumoko et al, 2015). Selenium and a number of other trace elements may also influence goiter development and general thyroid metabolism (Kishosha et al, 2011;Maouche et al, 2015;El-Fadeli et al, 2016;Gashu et al, 2016). Liver function may be compromised in nickel-plating workers (El-Shafei, 2011).…”
Section: Health Outcomesmentioning
confidence: 99%